Peranan Media Interaktif Dalam Pembelajaran Sejarah Peradaban Islam Bagi Gaya Belajar Visual Siswa - Fitrah Rahma Yani; Wahidah Fitriani (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Educational technology is a collection of media developments that are innovated in a complex and integrated manner for educational purposes. In this increasingly modern era, all students must be able to compete, so educators and students must prepare themselves with technological developments. With the increasing development of technology, this can support learning in schools, with technology it can expand learning resources across time and space. So, with the various characteristics and learning styles of students, it is hoped that technology can become a solution media in achieving educational goals. Of course, this must be utilized by educational institutions to maximize students' potential in facing the competitive era. This research uses a literature review method, with the aim of explaining the role of interactive media in learning the History of Islamic Civilization for students with a visual learning style. The research results show that interactive media has an important role for students with a visual learning style, apart from being able to maximize students' potential, interactive media can also be useful for educators to get relatively fast feedback in learning activities.